Dari halaman rumah ke Dewan Merak Kayangan: Upacara perkahwinan Melayu bandar - Fatimah Abdullah, (Universiti Kebangsaan Malaysia, 2009)
Every society has its own way of celebrating its important rites. It reflects not only integration, but also custom of the society. In traditional society mechanical solidarity is dominant, with its members participating in full force. But, in contemporary society, with the dominant feature of compartmentalization of the institutions, societal interaction is based on organic solidarity. This paper attempts to explain the changes taking place in the marriage and wedding ceremonies, as one of the manifestations of changes in social relations and interactions among family members. The views expressed is based on studies and observations in middle class Malay families in urban areas. The significance of the wedding ceremonies as a reflection of integration in the family is becoming less important as a consequence of many of wedding preparations are taken over by commercial agencies. As a result, wedding ceremony are is now more a manifestation of status symbol of the family concerned